Mecz o mistrzostwo I-ligi pomiędzy ŁTS Gliwice-ZKS Polonia. (Gdynia : [s.n.], 1966)
Afisz inf. o meczu 2.10.1966 r. w Hali Stoczni Gdańskiej.
Keywords: Stocznia Gdańska -- 1945-1970 -- druki ulotne; Boks -- Polska -- 1945-1970.